The antimicrobial activity of coenzyme Q0 against planktonic and biofilm forms of Cronobacter sakazakii. (April 2020) - Guo, Du; Wang, Shuo; Li, Jiahui; Bai, Fangting; Yang, Yanpeng; Xu, Yunfeng; Liang, Sen; Xia, Xiaodong; Wang, Xin; Shi, Chao
Abstract: Coenzyme Q0 (CoQ0 ) has demonstrated antitumor, anti-inflammatory, and anti-angiogenic activities. Cronobacter sakazakii is an opportunistic foodborne pathogen associated with high mortality in neonates. In this study, the antimicrobial activity and possible antimicrobial mechanism of CoQ0 against C. sakazakii were investigated. Moreover, the inactivation effect of CoQ0 on C. sakazakii in biofilms was also evaluated. The minimum inhibitory concentration (MIC) of CoQ0 against C. sakazakii strains ranged from 0.1 to 0.2 mg/mL. Treatment caused cell membrane dysfunction, as evidenced by cell membrane hyperpolarization, decreased intracellular ATP concentration and cell membrane integrity, and changes in cellular morphology. CoQ0 combined with mild heat treatment (45, 50, or 55 °C) decreased the number of viable non-desiccated and desiccated C. sakazakii cells in a time- and dose-dependent manner in reconstituted infant milk. Furthermore, CoQ0 showed effective inactivation activity against C. sakazakii in biofilms on stainless steel, reducing the number of viable cells and damaging the structure of the biofilm. These findings suggest that CoQ0 has a strong inactivate effect on C. sakazakii and could be used in food production environments to effectively control C. sakazakii and reduce the number of illnesses associated with it . Highlights: The antimicrobial effect of CoQ0 against C. sakazakii was assessed. CoQ0 caused cell membrane dysfunction. CoQ0 combined with mild heat treatment decreased viable cell numbers in RIF. CoQ0 inactivated C. sakazakii in biofilms on stainless steel.